Exploring the spread of English language learning in South Korea and reflections of the diversifying sociolinguistic context for future English language teaching practices. Issue 3 (2nd September 2019) - Jane Ra, Jaewon
ABSTRACT: The purpose of this article is to provide an understanding of why traditional English language teaching (ELT) which focuses on native speaker models has become obsolete in South Korea (henceforth Korea). Korea has been known as a linguistically and ethnically homogeneous nation throughout its history. However, the current sociolinguistic situation of Korea tells a different story. Various patterns of migration have emerged around the world and Korea has been no exception. This article explores the widespread passion for English language learning in Korea and the role of English on the individual and nationwide levels. Then, it argues that monolingual and standard language ideologies do not fit into this globalized era. Given the steadily diversifying demographics in Korea and the spread of global English, ELT in Korea ought to reflect English used in the 'real world'.